A Supramolecular Tubular Nanoreactor. Issue 28 (30th May 2014) - Li, Zhi‐Qiang; Zhang, Ying‐Ming; Chen, Yong; Liu, Yu
Abstract The extremely strong noncovalent complexation between the rigid host of phthalocyanine‐bridged β‐cyclodextrins and the amphiphilic guest carboxylated porphyrin is employed to construct a hollow tubular structure as a supramolecular nanoreactor. A representative coupling reaction occurs in the hydrophobic interlayers of the tubular walls in pure water at room temperature, leading to an enhancement of ten times higher reaction rate without any adverse effect on catalytic activity and conversion.